Legitimate Conditions for Usurpation of Authority in the Administrative Law - Mohammed Abdulkarim Sharif (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Usurpation of power is the term given to the defect of the gross lack of jurisdiction in the administrative law، and that the defect of usurpation of power afflicts the administrative decision، so it is stamped from the legal point of view and it transforms it from a legal work to a material work that has no effect on legal centers. However، the jurisprudence and the judiciary for certain considerations، including the functioning of public facilities and their non-stop، and the protection of people of good faith، giving life to the decision usurping power under certain conditions. Additionally، they considered it not only a legal act، but rather described it as legitimate as well، according to the situations that affect the administrative decision and from these situations if the administrative decision is found in the case of the actual employee and the case of exceptional circumstances. In addition، in some cases، the judiciary prohibits consideration of the legality of the decision even if it is tainted by the defect of usurpation of power، such as acts of sovereignty، and that this suggests its legitimacy even if it is a usurper of power.